ALLERGEN STANDARDIZATION - Hradilova, Sarka; Weigl, Evzen; Raska, Milan (Biomedical papers, 2000)
The article summarises current knowledge about the preparation and standardisation of treatment and diagnosisof allergies. It summarises the basic conceptions, units, methods and conditions for preparation, conservationand the storage of allergens. The article is especially orientated towards grass pollen.
Keywords: Allergen standardization / Grass pollen / Pollen allergen